Trade-Productivity-Institutional Nexus: Survey of Recent Literatures - Muhamad Iksan (Jurnal Manajemen dan Bisnis Madani, 2023)
Main task of this survey of literature to discuss satisfactory theoretical explanation over two questions: one is does trade policy cause productivity? Two is does institutional set-up of economic governance cause productivity? By taking Indonesian experiences, this paper tries to seed the light of international trade and productivity, based on the neoclassical and new institutional economic theory.  In order to address main task of this survey, it elaborates recent literatures that emphasizes on two strands. First part comes from trade policy which focuses to the strategic importance of firms, as main source of research data and main point of discussion. Besides that, this paper also reviews political institutions play their role in shaping the rule of games, broadly defined as institution and how the interest group influences trade policy, to protect special interest pro-free trade or pro-protectionist measures. Second part sheds light from the productivity literatures that cover the firm level and sector level productivity. Finally, this essay offers conclusions to sum up main argument of the paper.